Cultural Value Taxonomy of Eleven Siulak–Kerinci Folktales: A Codebook-Guided Content Analysis for Character Education in Junior Secondary Schools - Nada Sawita; Nazurty; Ade Kusmana; Desti Angraini (The Indonesian Institute of Science and Technology Research, 2026)
Indigenous folktales remain underutilized as structured resources for character education, especially as evidence-based value taxonomies for classroom use. This study develops a cultural value taxonomy from eleven Siulak-Kerinci folktales to support character learning in junior secondary schools. Using codebook-guided qualitative content analysis, the study treats meaning-complete narrative segments as units of analysis and applies explicit operational definitions, indicators, and inclusion–exclusion rules to identify cultural values. Cross-story comparison and negative case analysis were employed to refine categories and construct a hierarchical taxonomy. The findings reveal seven core value families embedded in the folktales: religiosity, honesty, responsibility, social care and mutual cooperation, work ethic, tolerance, and local identity. Each value family is represented through distinctive sub-indicators, while each folktale displays a particular pattern of dominant and supporting values. The resulting taxonomy provides teachers with a transparent framework for selecting stories, guiding reflective discussion, and designing value-focused assessment in classroom practice. Methodologically, the study shows that codebook-guided content analysis can transform local narratives into a systematic and culturally grounded value taxonomy that is both educationally applicable and useful for curriculum development and future comparative research.